Flexible robot sealant dispensing cell using RGB-D sensor and off-line programming - Maiolino, Perla; Woolley, Richard; Branson, David T.; Benardos, Panorios; Popov, Atanas A.; Ratchev, Svetan (Elsevier, 2017)
In aerospace manufacture the accurate and robust application of sealant is an integral and challenging part of the manufacturing process that is still performed by human operator. Automation of this process is difficult and not cost effective due to the high variability in the parts to operate and also the difficulty associated with programming industrial robotic systems. This work tries to overcome these problems by presenting an AOLP (Automatic Off-Line Programming) system for sealant dispensing through the integration of the ABB's proprietary OLP (Off-Line Programming) system RobotStudio with a relatively new RBG-D sensor technology based on structured light and the development of a RobotStudio add-on. The integration of the vision system in the generation of the robot program overcomes the current problems related to AOLP systems that rely on a known model of the work environment. This enables the ability to dynamically adapt the model according to sensor data, thus coping with environmental and parts variability during operation. Furthermore it exploits the advantages of an OLP system simplifying the robot programming allowing for faster automation of the process.